2018
DOI: 10.1080/10903127.2017.1399183
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of The I-Gel Supraglottic And King Laryngotracheal Airways In A Simulated Tactical Environment

Abstract: In a simulated tactical environment placement of the IGA for airway management was faster than with the KA, but there was no difference in regard to exposure. Additionally, all the participants preferred using the IGA device over the KA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Research published in 2018 showed that the average time for placement by paramedic students in a “simulated tactical environment” on high-fidelity manikins was 39.7 seconds with the King LTS-D versus 14.4 seconds with the i-gel [ 15 ]. The most recent ACLS guidelines emphasize the importance of high-quality chest compressions and limited interruptions [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research published in 2018 showed that the average time for placement by paramedic students in a “simulated tactical environment” on high-fidelity manikins was 39.7 seconds with the King LTS-D versus 14.4 seconds with the i-gel [ 15 ]. The most recent ACLS guidelines emphasize the importance of high-quality chest compressions and limited interruptions [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there is some limited data available comparing the two devices, there is minimal research about ease of use and FPS rate [ 15 ]. With current resuscitation guidelines emphasizing high-quality CPR with limited interruptions, it is important to identify the device that offers the most straightforward and reliable application.…”
Section: Introductionmentioning
confidence: 99%
“…This use of bag-valve-mask or pocket mask ventilation can be compared to other EMS where www.journals.viamedica.pl EMT`s use i-gel or other types of supraglottic devices [23]. Studies show how staff at basic EMT level successfully places various models of supraglottic devices [23,24]. But there is always a risk in using a supraglottic device since failure in securing the airway is associated with a prolonged hands-off chest time during the CPR [25].…”
Section: Ventilationmentioning
confidence: 99%
“…Recent evidence suggests that lowfidelity simulators excel at task familiarization and early skill development, occupying a vital role in the early learning of technical medical tasks [19]. For this reason, mannequins have been used in airway management education for over 50 years [20][21][22][23][24][25]. While these traditional models exist to allow medical learners practice in direct laryngoscopy, they do not quantify forces applied and may reinforce poor habits.…”
Section: Introductionmentioning
confidence: 99%